Observations of Pre-operative Teamwork and Communication During the Implementation of a City-Wide Surgical Safety Checklist - Hansen, Terry Leonid; Goerl, Kyle; Fears, Reginald; Nguyen, Tim; Hart, Traci; Uhlig, Paul (Kansas Journal of Medicine, 2012)
BACKGROUND: Use of the World Health Organization’s (WHO) perioperative safety checklist has been shown in prior studies to reduce morbidity and mortality. In 2009, the Medical Society of Sedgwick County, Kansas, developed a modified version of the WHO checklist for city-wide implementation. This study evaluated how the checklist was used at a Wichita hospital. METHODS: An observational tool was developed to evaluate time-outs at the beginning of surgical procedures. A convenience sample of cases was evaluated across surgical specialties and procedures. Observations included: 1) when the time-out was done, 2) who led the time-out, 3) which items on the checklist were addressed, 4) how much time was spent, and 5) whether problems were identified or adverse events prevented. RESULTS: Data were collected from 121 observations. Only one of the surgical teams was observed to refer directly to the checklist posted in the OR to conduct their time out. The time-out was done before induction (3%), drape (19%), incision (77%), and after incision (1%). The process was led by the circulating nurse (92%), surgeon (7%), and circulating nurse and surgeon together (1%). The percent of completed checklist items was: patient identity (96%), procedure (96%), antibiotics (87%), site (80%), allergies (75%), position (70%), equipment (60%), DVT prevention (50%), images (40%), surgeon concerns (36%), and anesthesia provider concerns (34%). On average, seven (SD = 2.5) of 11 items on the checklist were addressed. Time spent ranged from less than one minute to five minutes; 78% took one minute or less. Problems were identified in 7% of cases. In one case, a wrong site surgery was prevented. CONCLUSIONS: Despite the intention to implement a city-wide surgical safety checklist, the checklist rarely was used in its entirety to conduct the observed time-outs in the subject hospital. Although the checklist was under-utilized, safety benefits were observed from the time-out process. These would likely be enhanced and extended by consistent use of a checklist.